Women Delay Marriage in Malay Land - Marisa Elsera; Madinatul Munawarah; Sri Wahyuni; Casiavera (Journal of Sumatera Sociological Indicators, 2022)
There are many reasons to get married and there are many reasons not to marry. It is normal for marriage to be considered as a rational option, especially in metropolitan areas, but of course this cannot be normalized for people in small towns like Tanjungpinang where the majority are from the Malays. Modernity and the degradation of traditional values are the reasons why women delay marriage. Based on the results of the research, the Tanjungpinang Malay community can understand the delay in the age of marriage for working women (career women) but not so for women who do not work it is considered a disgrace.